Covid-19 pandemic: the challenges that Malaysian secondary school students faced with online learning / Nur Azlina Abd Aziz ... [et al.] - Abd Aziz, Nur Azlina; Mohd Mahyideen, Jamilah; Ranjethamoney Vijayarajoo, Angeline; Abd Aziz, Rossidah; Mohd Razali, Nur Hidayah (UiTM Cawangan Johor Kampus Pasir Gudang, 2020)
Most schools in Malaysia had been temporarily shut down as a consequence of the Covid-19 pandemic. This has changed the norm of education in schools dramatically whereby most teaching and learning were done on digital platforms. With this unplanned and sudden transition from traditional classroom settings to online learning, some are wondering whether these students could adapt to this transition. Therefore, this study focuses on challenges faced by Malaysian secondary school students with online learning.